Disengagement of dispersed cerium oxalate from nitric-oxalic acid medium in a batch settler: Measurements and CFD simulations. (1st September 2020) - Panda, Saroj K.; Vishnu Anand, P.; Aashranth, B.; Pandey, N.K.
Graphical abstract: Highlights: CFD simulations of solid–liquid disengagement in a batch settler and verification using measurements. Predictions of solid phase volume fraction along the settler height analyzed with the measured data. Positions of AI predicted for different constant particle size that corresponds to different impeller rotation. Adopted PSD methodology explained and measured for different impeller rotation and OSF. Abstract: The understanding of hydrodynamic characteristics and particle size distribution (PSD) of solid–liquid disengagement is crucial to design a continuous thickener for the reconversion step of nuclear fuel reprocessing. Disengagement of dispersed cerium oxalate from nitric-oxalic acid medium in a batch settler is experimentally investigated to find out solid volume fraction and PSD with different overall solid fraction followed by simulations to determine the position of active interface (AI). Eulerian-Eulerian simulations of the disengagement process were performed and the predicted solid phase volume fraction at different heights of the settler was verified using the experimental data. The predicted AI followed a good trend for different overall solid fraction. Owing to the constant particle size considered in the simulation, a difference between the predicted and measured solid phase volume fraction was observed. The predicted AI, measured solid volume fraction and PSD could aid the design of continuous thickener for nuclear fuel reconversion.